Critical Point Analysis for Sustainable Management of Cydia pomonella (Lepidoptera: Tortricidae) in Smallholder Walnut Farms of Catamarca, Argentina - Cavallo, María José; Castilla, María Cecilia; Barros, Lucas Ariel; Romero, Oscar Eduardo; Sosa, Braian Vladimir; Espinosa, Martin Sebastian; Diez, Patricia Alejandra (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2026)
In Argentina, 80% of walnut production is carried out by smallholder farms facing poor technology, production constraints, and substantial economic losses due to pests like Cydia pomonella (codling moth). We assessed sustainability risks linked to phytosanitary management on small farms in the Ambato region of Catamarca, Argentina. Our analysis included a “strong sustainability” framework with three key dimensions: ecological, economic, and sociocultural. A total of 26 indicators were related to this species’ management. Using semi-structured interviews, visual aids, and field surveys across seven farms, an overall sustainability index of 1.521 was calculated, with 50% of the indicators scoring below the established threshold (on a five-level sustainability scale, the selected threshold was level two). The ecological dimension emerged as the most sustainable. Limitations included absent systematic monitoring and optimisation of treatment timing, solely with agrochemical control, weak farmer-to-farmer collaboration, and insufficient training opportunities. Cluster analysis revealed four distinct groups based on phytosanitary practices. This study highlights critical intervention points and suggests agroecological strategies to enhance sustainable pest management in smallholder walnut systems. Highlights: A strong sustainability framework (ecological, sociocultural and economic) was applied to assess Cydia pomonellamanagement in smallholder walnut farms in Catamarca, Argentina. Sustainability was evaluated through 26 indicators using semi-structured interviews, visual tools, and field surveys. The overall sustainability index was low (1.521), with 50% of indicators falling below the acceptable threshold. Ecological practices showed comparatively higher sustainability, but suffered from lack of monitoring and weak communication between farmers. Cluster analysis indicated four distinct phytosanitary management profiles, suggesting targeted agroecological interventions.